Thin lateral wall cortex intertrochanteric proximal femur fractures: a comparative study between past and present - Abushahot, Mohammad Ahmad; Rousan, Fadi Mohammad; Shari, Naser Fuad; Alhseinat, Laith Mohammad; Al-Qudah, Ala Khaled (International Journal of Research in Orthopaedics, 2024)
Background: There has been a growing recognition of the significance of preserving the integrity of the lateral wall of the proximal femur, in addition to the previously emphasized importance of the posteromedial portion in predicting fracture stability. Consequently, this study aimed to compare the outcomes of various fixation methods employed in treating intertrochanteric proximal femur fractures with a thin lateral wall. Methods: This retrospective study assessed 225 cases of treated intertrochanteric fractures with a thin lateral cortex, examining radiological outcomes at different follow-up intervals to evaluate the efficacy of different treatments. The study compared Dynamic Hip Screw (DHS), Dynamic Condylar Screw (DCS), and Proximal Femoral Nail (PFN) in terms of healing, mortality, and complications. Results: The average age of patients was 79.75 years, with 61.3% having comorbidities. The three treatment modalities showed similar healing times, revision rates, and mortality rates. The one-year mortality rate stood at 26%. PFN consistently maintained a favorable position during follow-up assessments. While DHS initially exhibited excellent reduction on postoperative X-rays, less than half of the fractures maintained acceptable reduction during the first follow-up due to shaft medialization (32%) and varus collapse (24%). DHS treatment was also frequently associated with nonunion, with intraoperative lateral wall fractures occurring in 15.4% of cases. DCS was found to be the least effective treatment, being commonly associated with varus collapse. Conclusions: In treating intertrochanteric fractures with a thin lateral wall component, PFN demonstrated superior outcomes in terms of reduction and lower complication rates compared to other fixation methods. Therefore, PFN should be the preferred choice, while DHS and DCS should be avoided for this fracture pattern.